Toll-like receptor expression in crypt epithelial cells, putative stem cells and intestinal myofibroblasts isolated from controls and patients with inflammatory bowel disease. (4th September 2014) - Brown, M; Hughes, K R; Moossavi, S; Robins, A; Mahida, Y R
Summary: The aim of our studies was to investigate the expression of Toll-like receptor (TLR)-2 and TLR-4 (and in some studies TLR-5) in myofibroblasts and small and large intestinal crypt epithelial cells from control patients and those affected by Crohn's disease and ulcerative colitis. Isolated and disaggregated crypt epithelial cells and monolayers of myofibroblasts were used for studies by reverse transcription–polymerase chain reaction (RT–PCR), real-time RT–PCR, flow cytometry, immunocytochemistry and Western blot analysis. Compared to control cells, crypt epithelial cells isolated from active ulcerative colitis and Crohn's disease colonic mucosal samples showed significantly higher expression of TLR-2 and TLR-4 transcripts and protein (on the cell surface). There was also enhanced expression of TLR-4 in crypt cells from ileal Crohn's disease. Expression of TLR-2 and TLR-4 transcripts in crypt epithelial cells isolated from inflamed mucosa of distal ulcerative colitis did not differ significantly from such cells obtained from the normal proximal colon. Crypt epithelial cells with side population characteristics (putative stem cells) also expressed transcripts and protein for TLR-2, TLR-4 and TLR-5. Colonic myofibroblast expression of these TLRs was much weaker than in crypt epithelial cells. In conclusion, enhanced TLR-2 and TLR-4 expression by crypt epithelial cells in active inflammatory bowel disease likely reflects greater ability to respond to microbial products. Results from our studies using mucosal samples from patients with distal ulcerative colitis suggest that the enhanced expression of these TLRs could be constitutive. TLR-2, TLR-4 and TLR-5 expression by stem cells imply ability to respond to distinct bacterial products.